How customer satisfaction influences the frequency of purchases and experimentation on other sales channels in a retailer in brazil - de Araujo, Valéria Luisa Abreu; Morgado, Maurício Gerbaudo (Retail Management Review, 2023)
Object of analysis: Is the Net Promoter Score, an indicator used to assess customer satisfaction, also used as a performance indicator for its easy implementation, analysis and communication. Proposed by Frederich Reichheld (2003), this score works as a measure The objectives of this study were to identify whether this satisfaction score can influence customer consumption, investigate whether other sales channels end up being driven by this same factor, as well as whether there is variation in the average spend and CLV (Customer Lifetime Value) of customers according to NPS. Methodology used: Identified the relationship between the NPS score and customer loyalty, characterized by frequency of purchases, purchases in other company channels, average spending between promoter, neutral and detractor customers and also the value of CLV per customer, in a retail company in Brazil. The company studied has national coverage, is present in 22 Brazilian states with approximately 1,100 physical stores and strong participation in the e-commerce market. The company provided the customer base that responded to the NPS survey in 2019 and, based on queries from the company’s own database, the purchasing behavior of these customers in the year 2020 was raised. The tests: Were carried out to identify if there was a difference in the NPS scores between customers of the sales channels (physical stores and e-commerce) and also according to the gender of the customers, as well as to identify if promoting customers had a higher purchase frequency, higher spending medium, higher CLV and if they tried another sales channel, when compared to neutral customers and promoters. In general, it is possible to say that strong evidence was identified that customer satisfaction (measured by NPS) directly influences the frequency of purchases, average spending, CLV and the experimentation of other consumption channels for customers of physical stores. However, evidence has shown that for e-commerce customers, this difference between the same variables is non-existent between promoter, neutral and detractor customers.